Enhanced Cytotoxic Effects of Combined Valproic Acid and the Aurora Kinase Inhibitor VE465 on Gynecologic Cancer Cells - Li, Yanfang; Liu, Tao; Ivan, Cristina; Huang, Jie; Shen, De-Yu; Kavanagh, John J.; Bast,Jr, Robert C; Fu, Siqing; Hu, Wei; Sood, Anil (Frontiers in Oncology, 2013)
Increasing evidence shows that targeting epigenetic changes including acetylation and deacetylation of core nucleosomal histones as well as Aurora kinases hold promise for improving the treatment of human cancers including ovarian cancer. We investigated whether the histone deacetylase inhibitor, valproic acid (VPA) and the Aurora kinase inhibitor VE465 can have additive or synergistic effects on gynecologic cancer cells. We tested the in vitro antitumor activity of VPA and VE465, alone and in combination, in gynecologic cancer cells and assessed potential mechanisms of action. 3-[4,5-dimethyl-2-thiazolyl]-2,5-diphenyl-2H-tetrazolium bromide (MTT) analysis revealed that 72 hours of treatment with VPA or VE465 alone induced dose-dependent cytotoxic effects in nine gynecologic cancer cell lines (ovarian: 2008/C13, OVCAR3, SKOV3, and A2780; cervical: ME180 and CaSki; endometrial: HEC-1B; and uterine sarcoma: MES-SA and MES-SA/D×5). Co-treatment with VPA and VE465 enhanced cytotoxic effects on five of these cell lines: ovarian: 2008/C13, A2780, and OVCAR3; endometrial: HEC-1B; and cervical: ME180. In ovarian 2008/C13 cells, co-treatment with VPA (2 mM) and VE465 (1μM) induced more apoptosis than either VPA or VE465 alone. Western blot analysis showed that VPA alone increased the expression of cleaved PARP and p21 in a dose-dependent manner in 2008/C13 cells, while co-treatment with VPA and VE465 induced more cleaved PARP than treatment with VPA or VE465 alone did. The combined use of VPA and VE465 enhanced cytotoxic effects in some ovarian cancer cells, via enhanced induction of apoptosis. Targeting epigenetics with the histone deacetylase inhibitor, in combination with Aurora kinase inhibitors, holds promise for more effective therapy of ovarian cancer.